Impacts of coniferous bark-derived organic soil amendments on microbial communities in arable soil – a microcosm study. Issue 3 (1st February 2023) - Peltoniemi, Krista; Velmala, Sannakajsa; Fritze, Hannu; Jyske, Tuula; Rasi, Saija; Pennanen, Taina
Abstract: A decline in the carbon content of agricultural soils has been reported globally. Amendments of forest industry side-streams might counteract this. We tested the effects of industrial conifer bark and its cascade process materials on the soil microbiome under barley ( Hordeum vulgare L.) in clay and silt soil microcosms for 10 months, simulating the seasonal temperature changes of the boreal region. Microbial gene copy numbers were higher in clay soils than in silt. All amendments except unextracted bark increased bacterial gene copies in both soils. In turn, all other amendments, but not unextracted bark from an anaerobic digestion process, increased fungal gene copy numbers in silt soil. In clay soil, fungal increase occurred only with unextracted bark and hot water extracted bark. Soil, amendment type and simulated season affected both the bacterial and fungal community composition. Amendments increased bacteria originating from the anaerobic digestion process, as well as dinitrogen fixers and decomposers of plant cells. In turn, unextracted and hot water extracted bark determined the fungal community composition in silt. As fungal abundance increase and community diversification are related to soil carbon acquisition, bark-based amendments to soils can thus contribute to sustainable agriculture. Abstract : Bark-derived organic soil amendments affect fungal and bacterial gene copy numbers, their community composition and have the potential to increase microbes, promoting soil and plant health processes.